Determinants of the effective tax burden of companies in the Telecommunications activities in the Republic of Croatia - Bubanić Marijana (Sciendo, 2021)
The aim of this paper is to identify the determinants of the effective tax burden of companies in the activity division Telecommunication in the Republic of Croatia. The research covers the time interval from 2008 to 2017. Dynamic panel analysis was used to conduct the research. Microeconomic data were obtained from the databases of the Financial Agency, and macroeconomic data from the Central Bureau of Statistics. The results indicate that the effective tax burden of companies in the activity division Telecommunication is affected by the effective tax burden from the previous period, company size, leverage, inventory intensity, profitability and economic cycle. While capital and labour intensity didn`t prove statistically significant. The main limitations of the research lie in the impossibility of generalizing the stated results to all companies from the observed activity, using only one evaluation model, and being a cabinet-type research, without confirmation of the results obtained by companies. The research received several scientific contributions: this is the first study of the determinants of the effective tax burden conducted in the Republic of Croatia; the research covers an entire activity whit different companies sizes, and not as in most previous research, which mainly include only large companies listed on the stock exchange; unlike previous studies that used a balanced sample, and in most cases static panel models, this study used an unbalanced sample and a dynamic panel model.